من الشباب إلى الكبار: تعليم النحو بالمسجد بنجرماسين - Maulana, Muhammad Rifqi; Anaam, Nurullah Thorieq Faiz (Lugawiyyat, 2025)
This research aims to analyze Nahwu learning at Al-Faruq Mosque in Banjarmasin, focusing on teenagers to adults who do not have an Arabic background. This learning involves interaction between generations that differ in experience and mindset. This research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Results, the purpose of learning Nahwu is to understand the Qur'an and achieve Allah's pleasure. Learning activities are carried out every Friday after maghrib with material from the book “Ilmu Nahwu Praktis: Sistem Belajar 40 Jam.” Evaluation is based on the participants' understanding of Nahwu rules, ability to answer homework, and ability to distinguish isim, fi'il, and huruf, tested through exercises and direct questions to measure their overall ability. In conclusion, learning Nahwu at Al-Faruq Mosque has the potential to improve Arabic understanding among various ages, although there are challenges related to different levels of understanding and motivation.